1989
DOI: 10.1093/jn/119.10.1506
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Nippostrongylus brasiliensis Infection in the Zinc-Deficient Rat

Abstract: The role of zinc (Zn) in the immunological expulsion of the nematode Nippostrongylus brasiliensis (Nb) from the small intestine of the rat was investigated. Three groups of 28 rats each were fed a basal diet providing either 3 mg Zn/kg for the zinc-deficient group (-Zn) or 40 mg Zn/kg for ad libitum-fed and pair-fed controls. After 6 wk each group was divided into two equal subgroups and infected with either 1000 or 4000 infective Nb larvae/rat. The -Zn rats showed significant reductions (P less than 0.001) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…1Flattening of villi, which has been associated with zinc deficiency (Southon et al 1986), may facilitate early worm migration. Gross examination of our Zn" mice revealed a thin intestinal wall, which supports a similar observation in Zn" rats with Nippostrongylus brasiliensis infection (El-Hag et al 1989).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1Flattening of villi, which has been associated with zinc deficiency (Southon et al 1986), may facilitate early worm migration. Gross examination of our Zn" mice revealed a thin intestinal wall, which supports a similar observation in Zn" rats with Nippostrongylus brasiliensis infection (El-Hag et al 1989).…”
Section: Discussionsupporting
confidence: 87%
“…predict consequences of specific nutrient deficits on parasite biology given the complexity of the hostparasite interaction. Zinc deficiency, for example, is known to influence the immediate physico-chemical environment surrounding the intestinal parasites (El-Hag et al 1989) and the structure of the intestinal mucosa (Southon et al 1986), presumably making the host less than ideal for the parasite. However, zinc deficiency also impairs both non-specific and specific defence mechanisms (Cunningham-Rundles & Cunningham-Rundles, 1988;Fraker et al 1993), thus facilitating survival of the parasite (Shi et al 1994).…”
mentioning
confidence: 99%
“…In a study designed to examine the impact of zinc deficiency on Trichinella spiralis, Fenwick et al (1985) reported delayed expulsion and higher worm burdens in rats fed a zinc-deficient diet (3 mg zinclkg diet) compared with control animals. In contrast, in a well-controlled experimental study, El-Hag et al (1989) found that reduced dietary zinc (3mg zinclkg diet) had no effect on the number or size of Nippostrongylus brasiliensis in rats.…”
Section: Introductionmentioning
confidence: 83%
“…Zinc deficiency in rodents significantly impairs the capacity to mount an immunological response (Fraker et al, 1977(Fraker et al, , 1984(Fraker et al, , 1986Fernandez et ah, 1979), and it also affects the intestinal environment and morphology (Southon et al, 1986). Several studies on intestinal 'Present address: Research Department of Human Nutrition, Royal Veterinary and Agricultural University, Rolighedsvej 30, DK-1958 Frederiksberg C, Denmark + Author for correspondence nematode infections in rodent hosts (El-Hag et al, 1989;Fenwick et al, 1990a,b;Shi et al, 1994Shi et al, , 1995 have furthermore shown that zinc deficiency may result in impaired regulatory responses, as manifested through delayed expulsion, increased fecundity and an altered immune responsiveness. The consequences of zinc deficiency for the dynamics of nematode infections may thus be considerable, and indeed need to be evaluated in humans as well.…”
Section: Introductionmentioning
confidence: 99%